Flow analysis in cardiac chambers combining phase contrast, 3D tagged and cine MRI - Chabiniok, Radomir; Wong, James; Giese, Daniel; Nordsletten, David; Shi, Wenzhe; Greil, Gerald; Rueckert, Daniel; Razavi, Reza; Schaeffter, Tobias; Smith, Nic (Lecture Notes in Computer Science (including subseries Lecture Notes in Artificial Intelligence and Lecture Notes in Bioinformatics), 2013)
Accelerated methods for acquiring phase contrast (PC) MRI allow the acquisition of 4D flow data of the whole heart in clinically acceptable times. These datasets are becoming interesting both for clinicians - to better stratify diagnosis - and in the modeling community - to constrain patient-specific models. One of the difficulties related to PC data is a limited accuracy in the regions of low flow such as close to the myocardial wall, where the velocity field may even produce observed blood motion across the endocardial surface. To address this issue we propose to constrain the motion of blood in cavity during the analysis by using cine MRI and replacing the PC velocity in the peri-myocardial zone by neighboring tissue velocity obtained by analysis of 3D tagged MRI. We demonstrate the effect of these corrections on 2 healthy volunteer datasets and on one patient with a hypoplastic left ventricle. © 2013 Springer-Verlag.
CRIS-Team Scopus Importer:2023-03-08